A comparison of the diagnostic value of 2D strain stress echocardiography, myocardial perfusion scintigraphy, and Duke treadmill score in patients suspected of coronary artery disease. Issue 10 (11th July 2016) - Ejlersen, June A.; Poulsen, Steen H.; Mortensen, Jesper; May, Ole
Abstract : Background: Preinvasive risk stratification is recommended in patients suspected of coronary artery disease (CAD). Stress echocardiography (SE), myocardial perfusion scintigraphy (MPS), and exercise test are the dominant methods of choice. Vasodilator SE is fast and induces only minor increase in heart rate. The diagnostic value of the absolute stress–rest difference in endocardial global longitudinal strain (ΔeGLS) and wall motion (ΔWMI) from adenosine SE was compared to summed stress score (SSS) from MPS and Duke treadmill score (DTS) from exercise test, using quantitative invasive coronary angiography (ICA) as the reference. Methods and Results: A total of 128 patients (69% male, 62.7 (8.8) years) underwent adenosine SE, MPS, exercise test, and ICA. Forty‐five patients (35%) had CAD. All stress outcomes differed significantly ( P <.001) between patients with and without CAD: ΔeGLS: −1.3 (3.6)% vs −5.0 (3.3)%; WMI: 1.20 (0.34) vs 1.06 (0.13); SSS: 12.5 (8.2) vs 1.7 (3.6); and DTS: −3.4 (9.0) vs 3.9 (5.5). The cutoff values yielding the best sensitivity/specificity/accuracy were as follows: ΔeGLS: −2.3% or ΔWMI: 0 (69%/84%/79%), SSS: 4 (82%/94%/90%), and DTS: 1 (73%/78%/77%). The sensitivity of ΔeGLS + ΔWMI was similar to SSS ( P =.11) and DTS ( P =.59). The specificity of ΔeGLS + ΔWMI was inferior to SSS ( P =.03) and similar to DTS ( P =.28). Conclusion: Alterations in eGLS and wall motion during adenosine SE were closely associated with the presence of CAD and the combined sensitivity similar to that of MPS. If nuclear medical facilities are unavailable or radiation issues important, vasodilator ΔeGLS could be an acceptable alternative for patients unable to exercise.